Job profile of the human development graduate (Revista Electrónica REDINE, 2025)
The objective of this essay is to identify the areas of employment for graduates in human development. To this end, I rely on three main sources: 1. The document Degree in Human Development: Feasibility Study and Curriculum Design; 2. My knowledge, acquired through my role on the program’s leadership team, of the general areas of employment for these graduates; and 3. The areas of employment expressed by the graduates participating in the 18th anniversary celebration. As a final reflection, I argue that: The Degree in Human Development is a versatile program, that adapts to various scenarios in working life; this versatility is possible thanks to the multidisciplinary nature of its curriculum, among other factors, such as the graduates' own agency. As a result of this versatility, I identify the following areas of work: social responsibility, protection of vulnerable children, gender, human management, public administration, human security, human rights, human migration, among others; and that these areas occupy the three sectors: civil society (NGOs), the public sector, and the private sector.
Keywords: job profile; graduate in human development